Способ получения порошка, содержащего карбид кремния и нитрид алюминия, из золы природного угля - Пак А. Я. Александр Яковлевич; Мамонтов Г. Я. Геннадий Яковлевич; Губин В. Е. Владимир Евгеньевич; Васильева Ю. З. Юлия Захаровна
опубл. 28.08.2020